Diary of a wombat - French, Jackie; Whatley, Bruce (New York : Clarion Books, 2003)
In his diary, a wombat describes his life of eating, sleeping, and getting to know some new human neighbors.
Keywords: Wombats -- Juvenile fiction; Wombats -- Fiction; Diaries -- Fiction